The role of TGF? signaling in the formation of the dorsal nervous system is conserved between Drosophila and chordates. - Rusten, T.E.; Cantera, R.; Kafatos, F.C.; Barrio, R. (Development, 2002)
Transforming growth factor beta signaling mediated by Decapentaplegic and Screw is known to be involved in defining the border of the ventral neurogenic region in the fruitfly. A second phase of Decapentaplegic signaling occurs in a broad dorsal ectodermal region. Here, we show that the dorsolateral peripheral nervous system forms within the region where this second phase of signaling occurs. Decapentaplegic activity is required for development of many of the dorsal and lateral peripheral nervous system neurons. Double mutant analysis of the Decapentaplegic signaling mediator Schnurri and the inhibitor Brinker indicates that formation of these neurons requires Decapentaplegic signaling, and their absence in the mutant is mediated by a counteracting repression by Brinker. Interestingly, the ventral peripheral neurons that form outside the Decapentaplegic signaling domain depend on Brinker to develop. The role of Decapentaplegic signaling on dorsal and lateral peripheral neurons is strikingly similar to the known role of Transforming growth factor beta signaling in specifying dorsal cell fates of the lateral (later dorsal) nervous system in chordates (Halocythia, zebrafish, Xenopus, chicken and mouse). It points to an evolutionarily conserved mechanism specifying dorsal cell fates in the nervous system of both protostomes and deuterostomes.